(untitled) (Research Nepal Journal of Development Studies, 2021)
This article is about community mobilization in microcredit as a tool of women empowerment. It argues that women empowerment is a process and community mobilization is a tool for women empowerment process through micro-credit programs. This article is based on the views of selected key informants’ information through participant observation and a case study at Mahadevsthan Village in Dhading. Three local NGO managers and their three beneficiaries were conveniently selected for the sampling purpose. The main argument of the article shows that most of the females who received microcredit finally got socio-economic empowerment through acquiring access to capital, control over resources, self-esteem, confidence, decision-making power.